2004
DOI: 10.1002/bdra.20043
|View full text |Cite
|
Sign up to set email alerts
|

Developmental consequences of abnormal folate transport during murine heart morphogenesis

Abstract: Our findings demonstrate for the first time a prominent role of the Folbp1 gene in mediating susceptibility to heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 47 publications
1
59
0
1
Order By: Relevance
“…We observed that the phenotypic defects induced after a single exposure to Li during gastrulation (Chen et al, 2008) are similar to those reported by others for elevated HCy in a transgenic mouse model (Tang et al, 2004). Because of the similarities in the cardiac and neural anomalies induced by either HCy or Li exposure, and because Li is known to mimic Wnt-β-catenin signaling, we hypothesized that both HCy and Li may target canonical Wnt signaling during the same early developmental window, but that this modulation of the pathway occurs at different regulatory levels.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that the phenotypic defects induced after a single exposure to Li during gastrulation (Chen et al, 2008) are similar to those reported by others for elevated HCy in a transgenic mouse model (Tang et al, 2004). Because of the similarities in the cardiac and neural anomalies induced by either HCy or Li exposure, and because Li is known to mimic Wnt-β-catenin signaling, we hypothesized that both HCy and Li may target canonical Wnt signaling during the same early developmental window, but that this modulation of the pathway occurs at different regulatory levels.…”
Section: Introductionsupporting
confidence: 90%
“…Low dietary folate (folic acid, FA) and mutations in methylenetetrahydrofolate reductase (MTHFR) lead to elevated maternal plasma HCy levels. Elevated HCy increases the risk for neural tube, neural crest, craniofacial and congenital heart defects in the offspring (Boot et al, 2004;Huhta et al, 2006;Rosenquist et al, 1996;Tang et al, 2004). The association with elevated HCy is particularly strong for specific outflow tract defects, including pulmonary valve stenosis, coarctation of the aorta, and aortic valve stenosis (Huhta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may be suggested that FA treatment affects the expression of transcription factors and prevents the cardiac outflow tract defects. Furthermore, Tang et al reported that congenital heart defects in Folbp1 (-/-) mice were prevented by folic acid supplementation [39]. They demonstrated that this preventive effect is due to reduced apoptosis of cardiac neural crest cells that is associated with the expression of Pax-3 in cardiac neural crest cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies found that an impaired folate and homocysteine metabolism affect the neural crest cells formation and migration [1,26]. Tang et al( 2004) [27] observed that reduced availability of folate by inactivating the folate transporter, Folbp1, in mice leads to an extensive reduction of migrating cardiac neural crest cells. The authors observed neural crest cell-associated CHD, including the improper septation, persistent truncus arteriosus, and doubleoutlet right ventricle.…”
Section: Discussionmentioning
confidence: 99%